New Insights on Ferroptosis and Gynecological Malignancies - Fan, Ruiqi; Sun, Yujun; Wang, Mengxue; Wang, Qian; Jiang, Aifang; Yang, Tingting (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a new type of cell death different from apoptosis and necrosis, which can regulate the accumulation of lipid peroxidation through different pathways, ultimately leading to cell death. An increasing number of studies have revealed that the relationship between ferroptosis and cancer is extremely complex, which holds promise as a new treatment. In gynecological malignancies, ferroptosis has been found to have excellent antitumor activity, which can regulate the proliferation, metastasis and radiochemotherapy resistance. With the continuous progress of research, nanodrugs, gene therapy and other new therapeutic techniques for inducing ferroptosis have been proposed. However, the study of ferroptosis in gynecological malignancies is still in its infancy, and further research is needed to design safe and effective cancer therapies based on ferroptosis. This article reviews the mechanism of ferroptosis and the latest research progress and prospects in gynecological malignancies.